Transport impacts of government employment decentralization in an Australian city – Testing scenarios using transport simulation. (June 2017) - Li, Tiebei; Burke, Matthew; Dodson, Jago
Abstract: Australia's largest cities are more mono-centric than most US cities and may be over-centralising, particularly in terms of office employment. Government worker relocation programs are being employed with policy debate over what should be an ideal urban structure including in terms of travel behaviour. The paper explores research approaches to explore transport impacts of employment decentralization. A review shows the results of: surveys of workers moved to suburban locations; longitudinal analyses of transport and land use changes in city-regions using cross-sectional census or HTS data; comparative analysis of urban structure variables across cities using similar datasets; combinations of longitudinal and comparative research; and, scenario-based modelling approaches. A modelling framework is then developed to appraise the possible transport impacts of decentralization in Brisbane. To test the possibilities further, two decentralization scenarios modelled and compared. Decentralization mostly to middle-suburban locations better addresses jobs-housing balance and maximises proposed new public transport services, producing good transport outcomes. However, decentralization to outer-suburban locations in Brisbane exacerbates the propensity for decentralization to increase travel distances, especially by car. Highlights: Planned employment decentralization may help resolve the traffic congestion of a city with a mono-centric structure. Strong planning and government direction is required for success with employment decentralization. Transport modelling and simulation can assist the assessment of the potential impacts of employment decentralization.